2011
DOI: 10.11130/jei.2011.26.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Does More Trade Potential Remain in Arab States of the Gulf?

Abstract: This paper examines whether the Gulf Cooperation Council Countries (GCC) exerted any trade enhancing impact on its members by employing standard augmented gravity model as well as stochastic frontier gravity model. Panel data sets are constructed over the period of 1980 to 2008 for imports and exports of the bloc's main trading partners along with GCC countries. The major finding is that the trade enhancing effect of the bloc is significant. However, there is still huge unutilized trade potential between the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…References [16] use consumer price index (CPI) to represent the price level. Reference [10] suggested that the GDP deflator can be used in case CPI data is not available. We used GDP deflator as price indicator and its data is taken from WDI.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…References [16] use consumer price index (CPI) to represent the price level. Reference [10] suggested that the GDP deflator can be used in case CPI data is not available. We used GDP deflator as price indicator and its data is taken from WDI.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Reference [10] investigated whether Gulf Cooperative Council exert any trade enhancing impact on member countries, using standard gravity model and stochastic frontier gravity model from 1980 to 2008. The finding shows significant trade enhancing effect of GCC block.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Thirdly, alternative methods of calculating the potential trade value exist. Methods adopted in the studies of Kabir and Salim (2011), Pastore et al (2009), or Salim et al (2011) may serve as an example of a different approach. The afore-mentioned alternative methods may be used in the future to supplement the analysis conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The successful launch of the euro in 1999, solidified European economic integration and encouraged economists to investigate the integration potential of other regions. A number of regions, such as East Asia, the ASEAN, south Mediterranean countries, the East African Community (EAC), and the Gulf Cooperation Council (GCC) appeared as potential candidates for economic integration (Bayoumi & Eichengreen ; Salim et al ., ). East Asia, including the ASEAN countries, is often pronounced a highly credible optimum currency area.…”
Section: Literature Reviewmentioning
confidence: 97%